Ninth Workshop on Human-In-the-Loop Data Analytics (HILDA). - Chang, Remco.; Rong, Kexin.; Shraga, Roee. (Tufts University. Tisch Library., 2025)
Keywords: data analytics, data exploration, data management, data preparation, data visualization, human-centered computing, human-in-the-loop, information systems, labeling, large language models, machine learning.; Topic: Human-centered computing; Topic: Information systems / Data management systems; ACM Open.